The host gaze in global tourism - Moufakkir, Omar; Reisinger, Yvette (CAB International, 2013)
This book is about host-guest encounters in tourism, and specifically focuses on the host gaze. It identifies the aspects of the host gaze that distinguish it from the tourist gaze and from the conventional gaze encountered. It also identifies different types of host gazes and roles associated with them, as well as various categories of visitor that are recognized in the host gaze. The book analyses important religious, communal, cultural as well as psychological and emotional aspects of the host gaze. It shows how host communities construct, organize and systemize their gaze upon different tourists in different socioeconomic, political and cultural environments. The pre-existing cultural images of the host gaze and the differences in the host gaze across various geographical regions and nations are presented. The book has 16 main chapters and a subject index.